PELATIHAN CAREER READY PADA SISWA SMK SMTI MAKASSAR - St. Hadjar Nurul Istiqamah; A. Alifiya Tenriesa, Andi Ahmad Arif, Andi Indira Airai Putri (JOURNAL OF COMMUNITY DEDICATION, 2022)
SMK education in Indonesia is carried out to provide opportunities for students to work after graduating from school. Makassar SMTI Vocational School is a level of education directly supervised by the ministry of manpower that is oriented towards the industrial world. Because of this, students need debriefing in the form of career preparation (career ready) to face the world of work. The purpose of this training is to provide provisions for SMK SMTI Makassar students about themselves to prepare for the world of work. The method used is the provision of interventions in the form of training. The results found from this training are students get contributions of knowledge related to work preparation. After participating in the activity, 193 were satisfied with the training conducted.